Patterns of recurrence after radiation therapy for high-risk neuroblastoma - Jo, Ji Hwan; Ahn, Seung Do; Koh, Minji; Kim, Jong Hoon; Lee, Sang-wook; Song, Si Yeol; Yoon, Sang Min; Kim, Young Seok; Kim, Su Ssan; Park, Jin-hong; Jung, Jinhong; Choi, Eun Kyung (Radiation oncology journal, 2019)
To investigate the patterns of recurrence in patients with neuroblastoma treated with radiation therapy to the primary tumor site.PURPOSETo investigate the patterns of recurrence in patients with neuroblastoma treated with radiation therapy to the primary tumor site.We retrospectively analyzed patients with high-risk neuroblastoma managed with definitive treatment with radiation therapy to the primary tumor site between January 2003 and June 2017. These patients underwent three-dimensional conformal radiation therapy or intensity-modulated radiation therapy. A total of 14-36 Gy was delivered to the planning target volume, which included the primary tumor bed and the selected metastatic site. The disease stage was determined according to the International Neuroblastoma Staging System (INSS). We evaluated the recurrence pattern (i.e., local or systemic), progression-free survival, and overall survival.MATERIALS AND METHODSWe retrospectively analyzed patients with high-risk neuroblastoma managed with definitive treatment with radiation therapy to the primary tumor site between January 2003 and June 2017. These patients underwent three-dimensional conformal radiation therapy or intensity-modulated radiation therapy. A total of 14-36 Gy was delivered to the planning target volume, which included the primary tumor bed and the selected metastatic site. The disease stage was determined according to the International Neuroblastoma Staging System (INSS). We evaluated the recurrence pattern (i.e., local or systemic), progression-free survival, and overall survival.A total of 40 patients with high-risk neuroblastoma were included in this study. The median patient age was 4 years (range, 1 to 11 years). Thirty patients (75%) had INSS stage 4 neuroblastoma. At the median follow-up of 58 months, there were 6 cases of local recurrence and 10 cases of systemic recurrence. Among the 6 local failure cases, 4 relapsed adjacent to the radiation field. The other 2 relapsed in the radiation field (i.e., para-aortic and retroperitoneal areas). The main sites of distant metastasis were the bone, lymph nodes, and bone marrow. The 5-year progression-free survival was 70.9% and the 5-year overall survival was 74.3%.RESULTSA total of 40 patients with high-risk neuroblastoma were included in this study. The median patient age was 4 years (range, 1 to 11 years). Thirty patients (75%) had INSS stage 4 neuroblastoma. At the median follow-up of 58 months, there were 6 cases of local recurrence and 10 cases of systemic recurrence. Among the 6 local failure cases, 4 relapsed adjacent to the radiation field. The other 2 relapsed in the radiation field (i.e., para-aortic and retroperitoneal areas). The main sites of distant metastasis were the bone, lymph nodes, and bone marrow. The 5-year progression-free survival was 70.9% and the 5-year overall survival was 74.3%.Radiation therapy directed at the primary tumor site provides good local control. It seems to be adequate for disease control in patients with high-risk neuroblastoma after chemotherapy and surgical resection.CONCLUSIONRadiation therapy directed at the primary tumor site provides good local control. It seems to be adequate for disease control in patients with high-risk neuroblastoma after chemotherapy and surgical resection.